Efficiency of local self-governments in Serbia: an SFA approach - Radulovic, Branko; Dragutinović, Stefan (Industrija, 2015)
We examine the extent of inefficiency in a sample of 143 Serbian local self-governments for the year 2012. The input side is described by current expenditures of the local self-governments, and the outputs are describing provision of key public services. We use stochastic frontier approach. Our results reveal that the “average” local self-government in the Republic of Serbia produces public services i.e. output at costs that are approximately 23 percent higher than the ‘best practice’ peers; once we control for the exogenous constraints on public service provision. We provide a brief discussion of our results and guidance for future research.